1990
DOI: 10.2307/3869242
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Repression of Transcription in Higher Plants

Abstract: Using freshly isolated maize mesophyll protoplasts and a transient expression method, I showed that the transcriptional activity of seven maize photosynthetic gene promoters is specifically and coordinately repressed by the photosynthetic end products sucrose and glucose and by the exogenous carbon source acetate. Analysis of deleted, mutated, and hybrid promoters showed that sugars and acetate inhibit the activity of distinct positive upstream regulatory elements without a common consensus. The metabolic repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
368
6
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 260 publications
(397 citation statements)
references
References 21 publications
18
368
6
5
Order By: Relevance
“…A number of studies showed a loss of Rubisco total activity in leaves which accumulated soluble carbohydrates (Krapp etaL, 1991(Krapp etaL, , 1993Stitt, 1991;Van Oosten and Besford, 1995). This reduction in Rubisco activity was the result of a similar loss of Rubisco protein (Krapp etaL, 1993;Van Oosten and Besford, 1995) which was concomitant with a reduction in RBCS transcript (Criqui etaL, 1992;Krapp et aL, 1993;Van Oosten and Besford, 1995) and a repression of the transcriptional activity of a RBCS promoter (Krapp et aL, 1993;Sheen, 1989). The repression of RBCSand other genes by carbohydrates suggests a common mechanism of control of nuclear genes coding for photosynthetic proteins (Jang and Sheen, 1994;Jang etaL, 1997;Sheen, 1989Sheen, , 1994.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies showed a loss of Rubisco total activity in leaves which accumulated soluble carbohydrates (Krapp etaL, 1991(Krapp etaL, , 1993Stitt, 1991;Van Oosten and Besford, 1995). This reduction in Rubisco activity was the result of a similar loss of Rubisco protein (Krapp etaL, 1993;Van Oosten and Besford, 1995) which was concomitant with a reduction in RBCS transcript (Criqui etaL, 1992;Krapp et aL, 1993;Van Oosten and Besford, 1995) and a repression of the transcriptional activity of a RBCS promoter (Krapp et aL, 1993;Sheen, 1989). The repression of RBCSand other genes by carbohydrates suggests a common mechanism of control of nuclear genes coding for photosynthetic proteins (Jang and Sheen, 1994;Jang etaL, 1997;Sheen, 1989Sheen, , 1994.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, photosynthesis is inhibited when the production of photosynthates exceeds the rate of utilization by sinks, a sink being an organ which utilizes or stores carbohydrate generated by other parts of the plant. This was clearly shown in experiments in which the source-sink status of the plant was manipulated by reducing export out of the leaf (AzconBieto, t983; Blechmidt-Schneider et aL, 1989;Krapp et aL, 1991;Paul etaL, 1991;Plaut etaL, 1987). Tobacco plants expressing a yeast invertase in the apoplastic space had stunted growth, a clear carbohydrate increase and a strong inhibition of photosynthesis (von Schaewen etaL, 1991).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations